IMPLEMENTASI PROGRAM FAUNA AND FLORA INTERNATIONAL (FFI) DALAM KONSERVASI HUTAN KAWASAN ULU MASEN DI KECAMATAN MANE PROVINSI ACEH - Andina Fasha; Saiman Pakpahan (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2016)
This research will explain about program implementation from an international organization named Fauna and Flora International (FFI) in forest conservation at Ulu Masen, Mane area Aceh province. Illegal logging, woods areal conversion into plantations and farms, and the conflicts between humans and wild animals have been threatening the forests and could trigger disasters and declining the number of rare wild animal species at wood areal, especially Gajah Sumatera and Harimau Sumatera. As an international organization of conservation based in England who works in environmental issues, biological diversity, and climate change, FFI works together with the Aceh government, local institutions, and society to carry out conservation programs such as CRU (Conservation Response Unit), Pride Campaign, and agro-forestry training at Mane area’s forest which is part of Ulu Masen’s region.Sources were obtained through literature review from journals, books, mini thesis, reports, and internet to explain FFI’s planned programs. Writer also did an interview and observation by observing and taking notes of the indications systematically. The theories used in this research are pluralism, green politic theory, and forest reservation concept.This research indicates that implemented programs by FFI influencing the declining of illegal logging and increasing society’s awareness of the importance to keep the forests and preserve the biological diversity found in the forest.Keywords: Fauna and Flora International, Forest Threat, Conservation Program, Biological Diversity